Implikasi Yuridis Perubahan Kementerian/Lembaga pada Kabinet Merah Putih Terhadap Pelaksanaan Tindak Lanjut Rekomendasi Hasil Pemeriksaan Badan Pemeriksa Keuangan: Legal Implications of Reorganization of “Merah Putih” Cabinet to the Implementation of the Follow Up to Audit Recommendations of the Audit Board - Najib, Muh; Siregar, Desfreidna (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2025)
The formation of Indonesia’s Merah Putih Cabinet in 2024 has altered the composition and structure of several ministries and agencies, despite prior audits and recommendations by the Audit Board of Indonesia (BPK). This study analyzes the legal implications of such restructuring on the follow-up of BPK audit recommendations (TLRHP), employing normative juridical method, utilizing both statutory and conceptual approaches. The findings indicate that, according to Article 7, letter d, of BPK Regulation No. 2 of 2017, changes to ministries or agencies that affect the organization’s existence may render follow-up recommendations infeasible, subject to BPK's professional judgment. However, the legislation does not specify how TLRHP should be executed in entities that have undergone restructuring, nor does it define the criteria used by BPK to exercise professional judgment in such cases. From the perspective of the theory of authority, TLRHP can only be executed by officials authorized under the prevailing regulations to take the recommended actions. Furthermore, the theory of legal responsibility suggests that positional responsibility, as outlined in BPK's recommendations, can be transferred to the succeeding official or the official currently in charge. In contrast, the individual responsibility, as specified in BPK's recommendations, must be borne and carried out by the individual concerned.